FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN MURABAHAH PADA PERBANKAN SYARIAH DI INDONESIA - Yanis, Ahmad Samhan; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to analyze the influence of debt to equity ratio (DER), third-party funds (DPK), financing to deposit ratio (FDR), current ratio (CR), and return on assets (ROA) to the murabahah financing at Sharia banking in Indonesia. The results of this research show that: (1) debt to equity ratio (DER) have positive influence to the murabahah financing; (2) third-party funds (DPK) have positive influence to the murabahah financing; (3) financing to deposit ratio (FDR) have positive influence to the murabahah financing; (4) current ratio (CR) have positive influence to the murabahah financing; and (5) return on assets (ROA) have positive influence to the murabahah financing.Keywords: debt to equity ratio (DER), third-party funds (DPK), financing to deposit ratio (FDR), current ratio (CR), return on assets (ROA)